Acceptance and Commitment Therapy as a Novel Treatment for Eating Disorders: An Initial Test of Efficacy and Mediation. (July 2013) - Juarascio, Adrienne; Shaw, Jena; Forman, Evan; Timko, C. Alix; Herbert, James; Butryn, Meghan; Bunnell, Douglas; Matteucci, Alyssa; Lowe, Michael
Eating disorders are among the most challenging disorders to treat, with even state-of-the-art cognitive-behavioral treatments achieving only modest success. One possible reason for the high rate of treatment failure for eating disorders is that existing treatments do not attend sufficiently to critical aspects of the disorder such as high experiential avoidance, poor experiential awareness, and lack of motivation. These variables are explicit targets of Acceptance and Commitment Therapy (ACT). The current study examined the efficacy of an ACT-based group treatment for eating disorders by examining whether the addition of ACT groups to treatment-as-usual (TAU) at a residential treatment facility for eating disorders would improve treatment outcomes. TAU patients received an intensive residential treatment, while ACT patients received these services but additionally attended, depending on diagnosis, either ACT for anorexia nervosa groups or ACT for bulimia nervosa groups. Although individuals in both treatment conditions demonstrated large decreases in eating pathology, there were trends toward larger decreases among those receiving ACT. ACT patients also showed lower rates of rehospitalization during the 6 months after discharge. Overall, results suggest that ACT is a viable treatment option for individuals with eating pathology and further outcome research is warranted.